2015
DOI: 10.1007/s00330-015-3914-x
|View full text |Cite
|
Sign up to set email alerts
|

Early post-operative magnetic resonance imaging in glioblastoma: correlation among radiological findings and overall survival in 60 patients

Abstract: • Some kind of contrast enhancement may be found in most EPMR examinations. • Thin-linear enhancements in the EPMR may be considered benign findings. • The EOR evaluated in the EPMR may stratify prognostic groups of patients. • The subjective evaluation of the EOR performs slightly better than its quantification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…Some well-known prognostic factors are patient age, performance status, neurologic function, mental status, MGMT promoter methylation status, and extent of tumor resection. 5,11,12,[15][16][17][18][19][20][21][22] The evolution of the tumor between EPMR and PRMR could provide information about proliferative behavior that might lead to additional predictive information about the outcome after therapy. Our study provides a positive argument for this possibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some well-known prognostic factors are patient age, performance status, neurologic function, mental status, MGMT promoter methylation status, and extent of tumor resection. 5,11,12,[15][16][17][18][19][20][21][22] The evolution of the tumor between EPMR and PRMR could provide information about proliferative behavior that might lead to additional predictive information about the outcome after therapy. Our study provides a positive argument for this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Patients were stratified into 3 groups according to the extent of tumor resection: total resection, subtotal resection between 95%-100%, and subtotal resection Ͻ95%.…”
Section: Mr Imagingmentioning
confidence: 99%
“…Previous studies have evaluated the patterns of contrast enhancement on early post-operative MR (EPMR) examinations within three days of surgery, following the recommendation of Ekinci et al[11, 12, 21]. Majos et al[12] demonstrated that GBM patients with thin-linear enhancement pattern survived longer than those with thick-linear or nodular enhancement patterns (median overall survival: thin linear = 609 days, thick linear = 432 days, and nodular = 318 days).…”
Section: Discussionmentioning
confidence: 99%
“…Majos et al[12] demonstrated that GBM patients with thin-linear enhancement pattern survived longer than those with thick-linear or nodular enhancement patterns (median overall survival: thin linear = 609 days, thick linear = 432 days, and nodular = 318 days). Accordingly, this study suggested that a thin-linear enhancement pattern on EPMR could be considered a benign and favorable finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation